SUICIDOLOGY - COSMAN, Doina (2014)
Before being a medical concern, suicide imposed itself as a general human problem, implying the belief in the transcendent being and the sentiment of honor. The present work, the first compendium published in Romania, does not ignore this anthropological specification of the suicide, invoking historical data and contemporary studies. But the exceptional aspect of the work consists of exhaustively going through all the aspects under which suicide could be approached, not ignoring the genetic influences, the cerebral neurotransmission, statistics, the correlation – but not the overlapping – with mental pathology and many other directions of analysis. The reader will be captured by with the irresistible attraction force of a great work of art and will find himself enriched with solid scientific knowledge, written by a person who studied the subject thoroughly both from a theoretical and a practical point of view. Unavoidably, the publication of this book will be a turning point, it will offer to a large audience and various specialists an instrument for action which was missing so much in the cultural, social and medical landscape of our country.